2020
DOI: 10.1186/s12917-020-2253-6
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a truncated form of flagellin (TFlg) into porcine circovirus type 2 virus-like particles enhances immune responses in mice

Abstract: Background: Porcine circovirus type 2 (PCV2) is an economically important pathogen in the swine industry worldwide. Vaccination remains the principal tool to control PCV2-associated diseases (PCVADs). Current vaccines do not eliminate viral shedding in the environment. To enhance the efficacy of PCV2 vaccines, recombinant viruslike particles (VLPs) of PCV2 were generated by fusing a truncated form of flagellin FliC (TFlg: 85-111aa) with the PCV2 capsid protein (Cap). Results: The recombinant proteins were expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Similarly, VLP immunization in mice and guinea pigs was able to significantly induce specific antibody responses to PCV2 Cap [42]. Meanwhile, in another study [43], the protective immune responses of a VLP-based PCV2 vaccine enhanced by the incorporation of a truncated form of flagellin significantly reduced viral loads in lung samples from mice. PiCV viral loads in the spleens of naturally infected nonvaccinated pigeons were also reportedly higher than those of the naturally infected pigeons vaccinated with recombinant PiCV Cap vaccine formulation [1].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, VLP immunization in mice and guinea pigs was able to significantly induce specific antibody responses to PCV2 Cap [42]. Meanwhile, in another study [43], the protective immune responses of a VLP-based PCV2 vaccine enhanced by the incorporation of a truncated form of flagellin significantly reduced viral loads in lung samples from mice. PiCV viral loads in the spleens of naturally infected nonvaccinated pigeons were also reportedly higher than those of the naturally infected pigeons vaccinated with recombinant PiCV Cap vaccine formulation [1].…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, the VLP group displayed a T cell proliferation stimulation index that is twice higher and IFN-γ fold change that is thrice higher as compared with the control group. A similar study on PCV2 VLPs demonstrated that after the vaccination with VLP, the level of IFN-γ production was higher than with Cap vaccine [43]. Administration of VLPs enhanced the T helper type 1 (Th1), which promotes inflammatory responses through the secretion of cytokines such as gamma interferon (IFN-γ) that activate macrophages and provide help to CD8+ cytotoxic T cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potential to allow insertion or substitution of small fragments of foreign peptides of C terminal of PCV2 Cap without apparent negative effect on formation of VLPs. 19 , 37 In the present study, different DC-binding peptides were introduced into C-terminal of PCV2 Cap, and fusion proteins were expressed in soluble form. After one-step Ni-NTA affinity purification, Cap-DCbp fusion proteins form highly organized VLPs with similar morphology.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the titers of anti-PCV2 neutralizing antibodies (NAbs) in serum samples, VNT was performed as described previously. 19 Briefly, 4×10 5 PK-15 cells were pre-seeded into 96-well plates and cultured in DMEM containing 10% FBS at 37°C for 24 h. Heat-inactivated serum samples were 2-fold serially diluted to 1:256. 100 μL of each diluted sample was mixed with an equal volume of PCV JH (200 TCID 50 ) and added to the cells, and allowed to interact for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation